2014
DOI: 10.1016/j.jlumin.2014.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence spectroscopy and energy level location of lanthanide ions doped in La(PO3)3

Abstract: a b s t r a c tThe luminescence properties of Cewere studied by vacuum ultra-violet spectroscopy at 10 K which gives information on the energies of 4f-5d excitation and emission and charge transfer bands of the dopants. All data are consistent with available models and have been used to construct the vacuum referred binding energy scheme for all trivalent and all divalent lanthanides in La(PO 3 ) 3 phosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…3 H i (i = 4, 5, 6) and 3 F j (j=2, 4) (Zhou et al, 2012;Shalapska et al, 2014;Prasad et al, 2018;Runowski et al, 2019). Prasad et al (2018) identified the 1 D 2 state to be the transition origin for the prominent Pr emission at around 600 nm as well as Gaft et al (2005), who also attributed the emission around 500 nm to the same origin.…”
Section: Ree Reference Spectra At 442 Nm Laser Excitationmentioning
confidence: 95%
See 4 more Smart Citations
“…3 H i (i = 4, 5, 6) and 3 F j (j=2, 4) (Zhou et al, 2012;Shalapska et al, 2014;Prasad et al, 2018;Runowski et al, 2019). Prasad et al (2018) identified the 1 D 2 state to be the transition origin for the prominent Pr emission at around 600 nm as well as Gaft et al (2005), who also attributed the emission around 500 nm to the same origin.…”
Section: Ree Reference Spectra At 442 Nm Laser Excitationmentioning
confidence: 95%
“…The very broad emission is difficult to interpret based on our results and goes beyond the scope of this study. In general, it overlaps with the characteristic Ce 3+ emission band around 360 nm that is associated to a 5d -4f transition (e.g., Reisfeld et al, 1996;Gaft et al, 2005;Shalapska et al, 2014). Several studies report broadened Ce-related peaks and discuss reasons behind, e.g.…”
Section: Ree Reference Spectra At 325 Nm Laser Excitationmentioning
confidence: 99%
See 3 more Smart Citations